ANALYSIS OF THE READABILITY OF NOUN PHRASE TRANSLATION IN INDONESIAN CONSTITUTIONAL COURT NEWS - Putri Ratnasari; Nur Hasyim; Sujiwo Priambodo (LinguAmerta, 2025)
This study aims to examine the types of noun phrases in the form of election term collocations and evaluate the readability of their translations in institutional news texts from the Constitutional Court of the Republic of Indonesia. The noun phrases that are the subject of this study are classified into three types, namely, modificative, coordinative, and appositive noun phrases, based on Widjono's theory (2005). Electoral term collocations in the form of noun phrases such as election results, election stages, and electoral districts have specific structures and meanings, so their translation requires accuracy of meaning and ease of understanding in the target language. This study uses a qualitative descriptive approach with content analysis techniques and the distribution of readability questionnaires to 25 respondents. Data were collected from 12 online news articles from the Indonesian Constitutional Court discussing disputes over the 2024 election results, with a total of 80 noun phrases. The results show that the most dominant type of noun phrase is the modificative noun phrase. Additionally, most translations of these noun phrases are considered easy to understand by the target readers, with an average readability score of 2.77 on a scale of 3. These findings indicate that the translation of noun phrases in institutional texts has achieved a good level of readability, although there are still some noun phrases that could be confusing if not adapted to internationally recognized equivalents.